Achalasia Cardia: Short-term Results of 40 Iraqi Patients - Abdulsalam, Ahmed; Taha, Abdulsalam Y (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Achalasia is an uncommon but not a rare a malady. In Iraq, we lack true statistics about this condition. Objective: is to review the experience with trans-thoracic modified Heller operation for achalasia cardia in a major thoracic surgical centre in Iraq over a 4-year period. Study design: a combined retrospective and prospective study. Setting: Department of Thoracic Surgery in Baghdad Medical City/Baghdad/Iraq. Methods: This study is both retrospective (20 cases) and prospective (20 cases); the information is collected from either patients, case sheets or obtained directly from patients, interviews. In both situations, relevant demographic and clinical information is obtained. The patients then are subjected to a standard diagnostic workup followed by preparation of patients for surgery. A trans-thoracic modified Heller’s operation: esophagocardiomyotomy) is done following a standard technique. No anti-reflux procedure is added. Follow up is done to evaluate results of surgery.Patients: 40 patients (26 males and 14 females) with achalasia cardia who were admitted to the Department of Thoracic Surgery in Baghdad Medical City over a period of 4 years (2008 to 2012). Results: 26 males (65%) and 14 females (35%) with a mean age of 26.6 year. Patients aged 20 -40 years constituted the majority (47.5%). The commonest presenting symptom was dysphagia reported in 39 patients (75%). Cucumber dilated esophagus (rat tail sign) was the commonest appearance on contrast study found in 84% of studied patients. Ten patients (7 females and 3 males) had dilation therapy initially which failed to improve their symptoms thus scheduled for surgery. The remaining 30 patients were offered surgical treatment from the start; thus ultimately, operation was done to all 40 patients. Good to excellent results after surgery were obtained in 35 patients (87.5%). Conclusions: though good and excellent results followed Heller’s operation for achalasia cardia versus multiple forceful dilatations, laparoscopic Heller oesophageal myotomy reverses the symptoms of achalasia with minimal morbidity. It is recommended to learn and practice this minimal invasive procedure rather than to continue doing an old operation.